2020
DOI: 10.1136/bmjopen-2020-042122
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterisation of asymptomatic carriers of COVID-19 in Colombia: a cross-sectional study

Abstract: IntroductionAsymptomatic carriers (AC) of the new SARS-CoV-2 represent an important source of spread for COVID-19. Early diagnosis of these cases is a powerful tool to control the pandemic. Our objective was to characterise patients with AC status and identify associated sociodemographic factors.MethodsUsing a cross-sectional design and the national database of daily occurrence of COVID-19, we characterised both socially and demographically all ACs. Additional correspondence analysis and logistic regression mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The socioeconomic difficulties inherent to the country’s situation and the inadequate education and understanding of the public health context by the community, which results in an inappropriate perception of risk, are factors that have a negative impact on the management and effectiveness of the measures taken, which has facilitated the dispersion of COVID-19 [ 19 , 20 , 21 , 22 ]. Several epidemic modelling studies based on R t estimations have been performed in an attempt to decipher the current infection dynamics, with the caveat that most of these studies have been purely descriptive and restricted to certain geographical regions at the beginning of the pandemic [ 3 , 23 , 24 , 25 , 26 , 27 ]. This has precluded an accurate assessment on the impact of control strategies across wide settings throughout the pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…The socioeconomic difficulties inherent to the country’s situation and the inadequate education and understanding of the public health context by the community, which results in an inappropriate perception of risk, are factors that have a negative impact on the management and effectiveness of the measures taken, which has facilitated the dispersion of COVID-19 [ 19 , 20 , 21 , 22 ]. Several epidemic modelling studies based on R t estimations have been performed in an attempt to decipher the current infection dynamics, with the caveat that most of these studies have been purely descriptive and restricted to certain geographical regions at the beginning of the pandemic [ 3 , 23 , 24 , 25 , 26 , 27 ]. This has precluded an accurate assessment on the impact of control strategies across wide settings throughout the pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…21 The prevalence of asymptomatic cases was higher in men, in people younger than 20 years and in the elders. These differences, also observed in large hospital-based series 22 and in other studies 23 , may reflect either a distinct clinical presentation or different sensitivity to notice and report common unspecific symptoms. Interestingly, in general population studies, the number of symptoms reported is higher in women, 24,25 and tends to increase with age, 25 although with a slight decline in elder groups.…”
Section: Discussionmentioning
confidence: 71%
“…Despite the fact that there are some previous studies that link PA with either HRQoL, or with the quality of sleep and/or the reduction of depressive symptoms during the pandemic, to our knowledge, there have been no studies carried out in the middle-aged Colombian population who work in the university context, during the mandatory confinement caused by this pandemic. We emphasize that most of the investigations that have been carried out in the Colombian population, in this context, have examined aspects related to the biology of the virus, the epidemiology of the infection, the mortality of the infection, suicide risk, depression, perceived stress, resilience to disease and the impacts of infection on children and adolescents, and those who work in hospitals [ 65 , 66 , 67 ]. Therefore, there is clearly a gap in knowledge in relation to the population of interest that we are addressing.…”
Section: Discussionmentioning
confidence: 99%